2009
DOI: 10.1158/1940-6207.capr-08-0238
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Gene-Environment Interaction Reveals Altered Mammary Gland Gene Expression and Increased Tumor Growth following Social Isolation

Abstract: Clinical studies have revealed that social support improves the outcome of cancer patients, whereas epidemiologic studies suggest that social isolation increases the risk of death associated with several chronic diseases. However, the precise molecular consequences of an unfavorable social environment have not been defined. To do so, robust, reproducible preclinical models are needed to study the mechanisms whereby an adverse environment affects gene expression and cancer biology. Because random assignment of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 47 publications
7
100
3
Order By: Relevance
“…Thus, the postpubertal increase in mammary gland ERα protein levels may have been amplified in LMS mice (relative to BMS and TR mice) due to altered HPG axis functioning. Previous studies using postpubertal social isolation as a stressor have shown stress-related effects on mammary tumorigenesis despite unaltered ERα protein levels (37,38). It is clear that the perceived intensity and the timing of the stressor with respect to development are important factors that modulate the effects of stress on mammary tumor risk.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the postpubertal increase in mammary gland ERα protein levels may have been amplified in LMS mice (relative to BMS and TR mice) due to altered HPG axis functioning. Previous studies using postpubertal social isolation as a stressor have shown stress-related effects on mammary tumorigenesis despite unaltered ERα protein levels (37,38). It is clear that the perceived intensity and the timing of the stressor with respect to development are important factors that modulate the effects of stress on mammary tumor risk.…”
Section: Discussionmentioning
confidence: 99%
“…12,[26][27][28] Patients with TNBC have limited therapeutic options after completion of conventional chemotherapy. They suffer higher rates of relapse compared with patients with ER-positive breast cancer, with most recurrences occurring within the first 3 years of breast cancer diagnosis.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R Tmentioning
confidence: 99%
“…Moreover, first generation beta-blockers targeting both the β1 and β2 adrenergic receptors, while second generation drugs mainly target just β1 (this subtype is primarily expressed on the myocardium) which could have also confounded conclusions. Evidence from experimental studies suggests that psychological stress can drive metastasis (18)(19)(20)(21)(22)(23)(24). For example, when mice bearing human tumors were confined or isolated from other miceconditions that increase stress-their tumors were more likely to metastasize.…”
Section: Editorialmentioning
confidence: 99%